ANALISIS PERILAKU BOM BUNUH BERDASARKAN TEORI AGRESI DAN BUNUH DIRI SEBAGAI DETEKSI DINI RADIKALISME - Wildan Kholidul Firdaus (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2022)
In mid-May 2018 before ramadhan, not long after terror at Mako Brimob Depok, Indonesian people were shocked by a series of terrorist suicide bombings in various places in Surabaya which involved a family including school-age children as the perpetrators. Various figures and experts flocked to express opinions and theories, ranging from radicalism, extremism, even conspiracy theories. The onslaught of terror is also much associated with religion and certain understandings which of course only focus on the ideology of a group of people, and forget the actors as individuals with cognitive abilities who consciously choose to commit suicide bombing. This article is based on literature reviews of journals coming from various official sources and websites, each article selected to describe the theory of aggression and suicide in relation to suicide bombings. In this paper, the author wants to open up a few opportunities for the theories of aggression and suicide to explain the behavior of suicide bombing terror. The purpose of this article is to define the criteria of vulnerable individuals to be recruited to commit suicide bombings, raising our awareness to the social environment including the scope of education so that early prevention can be done.